Relevansi Kewibawaan dan Kewiyataan dengan Hasil Belajar Siswa - Abdillah Abdillah (Nadwa: Jurnal Pendidikan Islam, 2012)
This paper elaborates student echivement based on authority, education, and quality of students’ learning. The study shows that the relationship between authority, education, and quality of students’ learning activity toward learning result in middle school category is bigger than high or low school category. The quality of students’ learning activity is oppointed by authority and education implemented by the teachers in learning process. The authority, education, and quality of students’ learning have relation significantly to the student echivement. The relationship of authority, education, and quality of students’ learning is definitly difference in predicting their echivement. Trough authority and education in learning process, the student’s echivement can be increased. Abstrak Makalah ini mengkaji hasil belajar yang didasarkan pada kewibawaan dan kewiyataan. Kajian ini menunjukkan bahwa hubungan kewibawaan, kewiyataan dan mutu belajar terhadap hasil belajar siswa pada sekolah kategori sedang itu lebih besar daripada sekolah kategori tinggi dan rendah. Tinggi rendahnya mutu kegiatan belajar siswa ditentukan oleh faktor kewibawaan dan kewiyataan yang diimplementasikan oleh guru dalam proses pembelajaran. Kewibawaan, kewiyataan dan mutu kegiatan belajar siswa berhubungan secara signifikan terhadap hasil belajar siswa. Hubungan kewibawaan, kewiyataan dan mutu kegiatan belajar siswa berbeda secara nyata dalam memprediksi hasil belajar siswa. Melalui kewibawaan dan kewiyataan dalam proses pembelajaran siswa dapat ditingkatkan hasil belajarnya.